Characterization of Complications Associated with Open and Endoscopic Craniosynostosis Surgery at a Single Institution - Han, Rowland H. (J Neurosurg Pediatr, 2015)
OBJECT: We present a retrospective cohort study examining complications in patients undergoing surgery for craniosynostosis using both minimally invasive endoscopic and open approaches. METHODS: Over the past ten years, 295 non-syndromic patients (140 endoscopic, 155 open) and 33 syndromic patients (10 endoscopic, 23 open) met our criteria. Variables analyzed included: age at surgery, presence of pre-existing CSF shunt, skin incision method, estimated blood loss (EBL), transfusions of packed red blood cells (PRBC), use of intravenous (IV) steroids or tranexamic acid (TXA), intraoperative durotomies, procedure length, and length of hospital stay. Complications were classified as either surgically or medically related. RESULTS: In the non-syndromic endoscopic group, we experienced 3 (2.1%) surgical and 5 (3.6%) medical complications. In the non-syndromic open group, there were 2 (1.3%) surgical and 7 (4.5%) medical complications. Intraoperative durotomies occurred in 5 (3.6%) endoscopic and 12 (7.8%) open cases, were repaired primarily, and did not result in reoperations for CSF leakage. Syndromic cases resulted in similar complication rates. No mortality or permanent morbidity occurred. Additionally, endoscopic procedures were associated with significantly decreased EBL, transfusions, procedure lengths, and lengths of hospital stay compared to open procedures. CONCLUSIONS: Rates of intraoperative durotomies, surgical and medical complications were comparable between endoscopic and open techniques. This is the largest direct comparison to date between endoscopic and open interventions for synostosis, and the results are in agreement with previous series that endoscopic surgery confers distinct advantages over open in appropriate patient populations.